Diction And Contextualization of The Jews Verses In The Holy Qur’an; Text, Translation And Commentary Of Abdullah Yusuf Ali - Mardhatillah, Masyithah (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This study aims to explores Abdullah Yusuf Ali’s interpreted the Jews in his The Holy Qur’an: Text, Translation and Commentary. His interpretation becomes worth to discuss due to his profile as a Moslem officer of Great Britain which politically supported the contemporary Jews in Israel. Additionally, Yusuf Ali was the big fan of the concept of inter-faith dialogue. On the other hand, he was so proud of being a Moslem so that he wrote an English translation and commentary of the Koran in order international society can understand Islam well. This paper is going to show how Yusuf Ali put himself as a Moslem and at the same time, a Britain officer, (and also admirer) who also lived in non-Moslem milieus. The discussion will explore two parts. The first one is the diction used by Yusuf Ali to interpret the Jews verses, while the second is the contemporary contextualization on his interpretation on Jews verses into nowadays life. Using library research method through primary and secondary references combined with a hermeneutical approach, this paper comes to the following conclusion. First, there found five dictions to mention the Jews at the Jews verses, which are Jews, those who followed the Jewish law, those that stand on Judaism, those who follow the spirit of Moses and those who follow the Jewish scripture. Second, by the diverse diction, Yusuf Ali implied that The Jews is all about the spirit and physical action of individual instead of religious institution or affiliation.